PERBEDAAN KEANEKARAGAMAN MAKROBENTOS SEBAGAI INDIKATOR BIOLOGI PENENTUAN KUALITAS AIR DI AREA PERKOTAAAN DAN DI PEDESAAAN LAMPUNG - Santoso, Teguh; Sutanto, Agus (BIOLOVA, 2021)
This has not been known as a comparison of macrobentos diversity between rural and urban areas. Based on this, it is necessary to analyze the comparison of Macrobentos in the urban area with rural areas. The river which is in the analogues of urban areas is the river Way Belau (Bandar Lampung) and the river Well Putri (Bandar Lampung), while the river which is in the area of the river in the countryside is the Pasir Sakti (East Lampung) and the River Raman Pujodadi (Trimurjo). The purpose of this study is to compare the diversity of Macrobentos in urban areas with rural areap. The type of research in this article is descriptive. The conclusion of this study is that there is a difference in the diversity of macrobentos between rivers that exist in rural areas with rivers that exist in urban areas. The rivers in the village area nudge have more macro-bentos diversity compared to existing rivers in urban areas.